THE USE OF INTERACTIVE TECHNIQUES IN NATIVE LANGUAGE LESSONS - Boboyev Yusuf Beknazarovich (American Journals Publishing, 2023)
Since the process in the long duration of Education is dead, its quality is closely related to the methods used in the lesson. The meaningful passage of the lesson, what methods are used in it and the result is achieved, determines the potential of the teacher, the level of the recipient. This article presents examples of interactive techniques that are recommended for use in native language lessons.
Keywords: intefaol, innovative technology, Carpenter, presentation method, selection, optional, performance, mandatory, opportunity, method, technology.